Preoperative prognostic nutritional index and systemic immune‐inflammation index predict survival outcomes in osteosarcoma: A comparison between young and elderly patients. Issue 4 (22nd November 2021) - Ma, Cong; Yu, Ronghui; Li, Junhong; Guo, Jingjing; Xu, Jianyun; Wang, Xiaoyan; Liu, Ping
Abstract: Objective: This retrospective study of patients with osteosarcoma investigated the following biomarkers of inflammation and nutritional status: neutrophil‐to‐lymphocyte ratio, platelet‐to‐lymphocyte ratio, prognostic nutritional index (PNI), and systemic immune‐inflammation index (SII). The efficacies of these indicators to predict overall survival (OS) of young and elderly patients were compared. Methods: The data of 125 patients with osteosarcoma, comprising the young (≤20 years) and elderly (60–80 years), were reviewed. Receiver operating characteristic (ROC) curves were calculated to determine the optimal cut‐off value and area under the ROC curve of each potential biomarker. Kaplan–Meier curves and a Cox proportional hazards model were used to perform survival analyses. Results: The cut‐off values for low and high PNI ( ≤48.5, >48.5) and low and high SII (≤607.3, >607.3) were determined. Osteosarcoma patients in low PNI group or high SII group exhibited poorer OS relative to those in high PNI or low SII groups. The univariate and multivariate analyses indicated that preoperative PNI and SII were independent prognostic factors for OS in both the young and elderly subjects. Conclusion: Preoperative PNI and SII can be viable biomarkers of prognosis for both young and elderly patients with osteosarcoma. Awareness of these valuable indexes will enable clinicians to evaluate the inflammatory and nutritional status of these patients and establish a framework for individualized therapy.